Educação socioemocional no currículo da educação integral do município de Araraquara -SP: uma análise documental - Santos, Patrícia Fiais Pereira dos (2024)
This research is a master's dissertation, linked to the Professional Postgraduate Program in Education of the Federal University of São Carlos, and aimed to study and investigate the theme of socioemotional education in the official curriculum of the city of Araraquara-SP, as well as to identify which elements of this document can enhance and which elements can hinder the socioemotional development of students in the comprehensive education program of the city of Araraquara. To this end, the study was carried out based on the documentary analysis of some productions on curriculum and curricular guidelines and legislation regarding socioemotional education. We consider that socioemotional education, when prioritized, is undoubtedly a potentializing agent in the process of student development, as different research in the area has pointed out. To this end, we first conducted a literature review focused on the topic and then, based on the guiding documents for comprehensive education in the city of Araraquara, we sought to understand which actions within the school are important for the construction of socio-emotional intelligence as well as the strengthening of emotions for intellectual development and personal and interpersonal relationships. The documentary analysis was carried out through a qualitative methodological approach, which is in line with the research's intention. The results of this study indicated the relevance of socio-emotional education in the development of children and adolescents, as well as the workshops of comprehensive education in Araraquara that favor the development of competence. The work was successful in verifying that the comprehensive education curriculum in Araraquara contributes to cognitive and socio-emotional development, elevating its students to a human formation, which values life in society, the strengthening of emotions, personal and interpersonal relationships, as well as behaviors that meet the characteristics necessary for the construction of an empathetic, emotionally strengthened society based on values of common well-being.